Efficacy and safety of the commercial Chinese polyherbal preparation Liu Shen Wan as an adjunctive treatment for herpes zoster and postherpetic neuralgia: a systematic review and meta-analysis - Li, Yajing; Zhang, Le; Wang, Wenya; Zhao, Hui; Liao, Xing (Frontiers in Pharmacology, 2025)
BackgroundLiu Shen Wan (LSW), a commercial Chinese polyherbal preparation (CCPP), is frequently utilized as an adjuvant treatment for herpes zoster and postherpetic neuralgia (HZ and PHN). Nevertheless, the clinical efficacy and safety of this treatment remain uncertain.PurposeThis study aims to systematically evaluate the efficacy and safety of LSW as adjunctive treatment in treating HZ/PHN.MethodsA comprehensive search was conducted across PubMed, Web of Science, Embase, Cochrane Library, ClinicalTrials.gov, and four Chinese databases. Eligibility criteria (PICOS) included the following: (1) patients with HZ/PHN; (2) LSW as adjunctive therapy (experimental group); (3) conventional treatment only (control group); (4) primary outcomes: vesicle cessation, scab formation, VAS, and PHN incidence; secondary outcomes: scab shedding time, time to pain resolution, duration of pain persistence, PHN efficacy, and adverse reactions; and (5) RCTs. Risk of bias was assessed using ROB 2.0, and data synthesis/analysis used RevMan 5.4. No restrictions on language.ResultsA total of 21 RCTs (n = 1,478) were included. Meta-analysis demonstrated that LSW plus conventional treatment significantly outperformed conventional treatment alone in shortening vesicle cessation time [MD = −1.44, 95% CI (−1.66, −0.93), p < 0.00001, I2 = 70%], accelerating scab formation (MD = −1.72, 95% CI (−2.09, −1.35), p < 0.00001, I2 = 38%), reducing scab shedding time (MD = −2.22, 95% CI (−3.64, −0.80), p = 0.002, I2 = 36%), decreasing time to pain resolution (MD = −2.46, 95% CI (−3.52, −1.39), p < 0.00001, I2 = 0%), and shortening pain persistence duration (MD = −1.97, 95% CI (−2.49, −1.46), p < 0.00001, I2 = 86%). Additionally, the combination therapy reduced PHN incidence (RR = 0.24, 95% CI (0.10, 0.57), p = 0.001, I2 = 0%), improved PHN efficacy (OR = 6.11, 95% CI (2.91, 12.82), p < 0.00001, I2 = 61%), and lowered adverse reactions (RR = 0.60, 95% CI (0.37, 0.96), p = 0.03, I2 = 0%). No serious drug-related adverse events were reported.ConclusionAdjunctive LSW therapy demonstrates potential to shorten herpes lesion healing time, improve treatment outcomes, and effectively prevent postherpetic neuralgia compared to conventional treatment alone. It also significantly reduces both the duration of pain and the overall disease course. Nevertheless, limitations in the current evidence base, including study quality and quantity, necessitate further rigorous investigation to confirm the long-term efficacy and safety profile of this combined intervention.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/, identifier CRD42024595203.